Upaya Yang Dilakukan Orang Kristen Dalam Meningkatkan Kerohanian - Septiniar Laoli; Martin Putra Hura (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
The reasons why Christians find it difficult to mature spiritually include: 1) slowness to listen, 2) feeling that they already know, 3) hardening their hearts against God's words, 4) believing because they only want to get blessings, and 5) their first love for God has faded. The purpose of this research is to study and understand the efforts made by Christians in improving their spiritual life and the benefits are to provide better insight and understanding of effective practices in improving the spiritual life of Christians. Furthermore, the research method used by this author is a descriptive qualitative research method through library research related to "How Believers Improve Spirituality". In addition, the focus of discussion in this study is to provide understanding to believers in improving spirituality through prayer, reading the Bible, worship, and participating in church services. This research can also provide valuable input for churches and spiritual leaders in providing more effective mentoring and teaching for the spiritual growth of the congregation.